Stylistics; Pragmatics; Ideology; Modality; Point of View; Coppe, Abiezer; - Borgogni, Daniele (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
The article proposes a pragmatic-stylistic analysis of modality and ideology in Abiezer Coppes Coppes Return to the Wayes of Truth(1651), a dramatic recantation written in prison by one of the most (in-)famous radical thinkers of England during the Interregnum. As the analysis will try to show, the peculiar features of this text and its complex communicative strategies call for a wider variety of methodological tools, complementing the application of code-driven models for the analysis of modality with more use-driven pragmatic and stylistic frameworks. In Coppes text, textual and contextual elements are as fundamental as code and grammatical aspects to convey evaluation, and they trigger a very sly conflict between overt and covert meanings, producing interstitial, ironical, even subversive reading possibilities, thus demonstrating how modality is inextricably tied to a variety of linguistic devices to produce a multifaceted message.